Comparison of Monitored Anesthesia Care with Propofol Versus Dexmedetomidine for Awake Craniotomy: A Retrospective study - Thakkar, Keta; Mariappan, Ramamani; Prabhu, Krishna; Yadav, Bijesh; Singh, Georgene (Journal of Neuroanaesthesiology and Critical Care, 2022)
Background Anesthetic agents used for awake craniotomy should be safe, short-acting, titratable, and provide an adequate level of sedation and analgesia, along with facilitating adequate neurological assessment during the functional testing. Our study aims to review the efficacy and safety profile, along with the potential for neurophysiological monitoring, of two commonly used anesthetic regimens, i.e., propofol and dexmedetomidine.Methods After the Ethics Committee approval, a retrospective analysis of 51 patients who underwent awake craniotomy for brain tumor excision over a period of 7 years was done. Those who received monitored anesthesia care (MAC) were divided into two groups, namely, Group P for that received propofol, and Group D that received dexmedetomidine and their hemodynamic profile, perioperative complications, neuromonitoring techniques, and postoperative course was noted from the records.Results A total of 31 patients were administered MAC with propofol and 20 with dexmedetomidine. The baseline demographic data, duration of surgery, intensive care unit (ICU), and hospital stay were comparable between the two. The hemodynamic profile as assessed by the heart rate and blood pressure was also comparable. The incidence of intraoperative seizures was found to be less in Group P, though. Episodes of transient desaturation were observed more in Group P (9.7%) than in Group D (5%), but none of the patients required conversion to general anesthesia. Direct cortical stimulation was satisfactorily elicited in 80% in Group P and 85% in Group D.Conclusion MAC with propofol and dexmedetomidine are acceptable techniques with comparable hemodynamic profile, intraoperative and postoperative complications, and potential for neurophysiological monitoring.
Keywords: awake craniotomy; eloquent area; propofol; dexmedetomidine; scalp block; seizures